2012
DOI: 10.1093/molbev/msr320
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Population Dynamics of Dengue Viruses in the Americas

Abstract: Changes in Dengue virus (DENV) disease patterns in the Americas over recent decades have been attributed, at least in part, to repeated introduction of DENV strains from other regions, resulting in a shift from hypoendemicity to hyperendemicity. Using newly sequenced DENV-1 and DENV-3 envelope (E) gene isolates from 11 Caribbean countries, along with sequences available on GenBank, we sought to document the population genetic and spatiotemporal transmission histories of the four main invading DENV genotypes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
108
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 44 publications
12
108
1
1
Order By: Relevance
“…For instance, the EV report for the United States indicated a singular CVB5 epidemic pattern with sharp increases at 3-to 6-year intervals. Our data also emphasize the ability of coalescence-based models (41) to depict the complex epidemic patterns of EV infections from genetic data, as reported earlier for other widespread RNA viruses (58).…”
Section: Discussionsupporting
confidence: 84%
“…For instance, the EV report for the United States indicated a singular CVB5 epidemic pattern with sharp increases at 3-to 6-year intervals. Our data also emphasize the ability of coalescence-based models (41) to depict the complex epidemic patterns of EV infections from genetic data, as reported earlier for other widespread RNA viruses (58).…”
Section: Discussionsupporting
confidence: 84%
“…This was particularly evident for L3, L6, L1a, L1b, L6-BR and isolates within L6-BR obtained in the Southeast Region of Brazil. This pattern is similar to the pattern observed by Allicock et al [51], who demonstrated that the MRCAs of all DENV serotypes were estimated to exist for several years (between 2 and 4 years, or 2 years in the case of DENV-1) prior to the first reported outbreaks for each serotype. These findings can be explained by the possibility of viruses remaining undetected until a threshold number of infections/disease incidences is reached that can be detected by the limited surveillance systems of most countries in the Americas [51].…”
supporting
confidence: 89%
“…Indeed, mean substitution rates for the four DENV serotypes ranging from 7.8 × 10 -4 to 9.9 × 10 -4 substitutions/site have been reported by Allicock et al [129], and comparable values have also been obtained in previous studies [128,130]. This considerable diversity is illustrated by the fact that several genotypes (with unique genetic future science group www.futuremedicine.com signatures) are currently defined for all existing DENV serotypes, and interactions and competition between these different genotypes may have serious epidemiological implications.…”
Section: Dengue Virusmentioning
confidence: 78%